Affinity-Enhanced Multimeric VEGF (Vascular Endothelial Growth Factor) and PlGF (Placental Growth Factor) Variants for Specific Adsorption of sFlt-1 to Restore Angiogenic Balance in Preeclampsia. Issue 4 (October 2020) - Matin, Mahsa; Mörgelin, Matthias; Stetefeld, Jörg; Schermer, Bernhard; Brinkkoetter, Paul T.; Benzing, Thomas; Koch, Manuel; Hagmann, Henning
Abstract : Preeclampsia is a potentially life-threatening multisystem disease affecting 4% to 8% of pregnant women after the 20th week of gestation. An excess of placental expressed antiangiogenic soluble VEGF (vascular endothelial growth factor)-receptor 1 (soluble FMS-like tyrosine kinase 1) scavenges VEGF and PlGF (placental growth factor), causing generalized endothelial dysfunction. Interventions to restore the angiogenic balance in preeclamptic pregnancies are intensively studied and improve maternal and neonatal outcomes. Especially extracorporeal strategies to remove sFlt-1 are promising in human pregnancy. However, available apheresis systems adsorb sFlt-1 unspecifically and with low efficiency. Affinity-enhanced ligands are needed to improve performance and compatibility of apheresis treatments. Using computerized molecular modeling, we developed multimeric VEGF molecules comprised of single-chain VEGF 165 dimers (scVEGF 165 ). A short peptide linker hampers intrachain dimerization to induce assembly preferably as tetrameric molecules as visualized in negative staining electron microscopy. scVEGF 165 multimers possess 1.2-fold higher affinity for sFlt-1 as compared to the available antibodies or monomeric VEGF. Consequently, scVEGF multimers have the ability to competitively release sFlt-1 bound PlGF and, in particular, VEGF. In ex vivo adsorption experiments using serum samples from patients with preeclampsia, scVEGF multimers reduce sFlt-1 levels by 85% and increase PlGF and VEGF levels by 20- and 9-fold, respectively. Finally, performance and stability of sFlt-1 capturing scVEGF 165 multimers were scrutinized on different matrices of which biocompatible agarose matrix yielded optimal results. We introduce the first VEGF-based highly efficient sFlt-1 apheresis system that is directly applicable in vivo due to utilization of inert agarose matrix, using a homomultimeric form of VEGF 165 to restore the angiogenic balance in preeclampsia. Abstract : Supplemental Digital Content is available in the text.